Fit for succession - community structure and life strategies of leafhoppers in urban brownfields - STRAUSS, BARBARA; BIEDERMANN, ROBERT (Ecological entomology, 2008)
1. Urban brownfields offer an excellent opportunity to study successional processes. Changes in the frequencies of biological traits during succession are of particular interest. They shed light on the general reasons why species emerge and vanish during the course of succession. 2. Leafhopper (Hemiptera: Auchenorrhyncha) occurrence data (3763 species observations) of 194 species were studied. Data was collected on 246 brownfield plots, aged 0-40 years, in two cities in Northern Germany. 3. Four categorical traits were studied: host-plant type, phagy, dormancy, and voltinism. In these traits, two aspects were analysed: (1) changes in trait category frequencies during succession, and (2) distribution of trait categories (i) within the brownfield species pool versus the German species pool and (ii) within species observations. 4. Trait categories showed clear successional trends. Young successional stages were related to feeding on herbs, polyphagy, egg overwintering, and two generations per year. 5. By analysing combinations of two traits, species could be assigned to four functional groups: species associated with young, intermediate and old sites, and one group indifferent to site age. The pioneer group comprised the least number of species, but the highest number of observations. 6. Categories associated with young site age were over-represented in the brownfield species pool. Moreover, within this already biased species pool, species with pioneer trait categories occurred with higher frequency. For the slow colonisers among leafhoppers, brownfields seem to be habitats that are hard to exploit.